Critical Optimism: A Methodological Posture to Shape the Future of Digital Social Research - Amaturo, Enrica; Aragona, Biagio (Italian Sociological Review, 2021)
In this paper we focus on the concept of critical optimism, a concept that has served many authors to explain orientation about the future. It means to be neither mechanistic in our imagination of the world nor naïve about the expectations the future can hold. Recently scholars have appealed to critical optimism to explain how we should relate to the digital, since when facing technology often, also in the scientific literature, we find extreme opinions. After ten years that the debate around technology and social research has developed on these two opposite visions, we promote an active engagement in testing the different instruments of digital research. Digital methods and big data must be integrated with traditional data sources and methods already existing in social sciences, and that is the right way to effectively improve the unfolding of social phenomena. In support of this thesis, we want to bring two examples that can demonstrate how the use of digital technologies did not lead to abandoning the traditional techniques of social research, but it instead has contributed to solving some problems in the use of these techniques, which before digital were hard to solve. Here, we will illustrate just two examples, the survey and the experiment, that relate to quantitative research, although certainly there are others that can be retraced in quantitative as well as qualitative research.